Revolutionizing pediatric neuroblastoma treatment: unraveling new molecular targets for precision interventions - Zheng, Min; Kumar, Ankush; Sharma, Vishakha; Behl, Tapan; Sehgal, Aayush; Wal, Pranay; Shinde, Nirmala Vikram; Kawaduji, Bhosale Sachin; Kapoor, Anupriya; Anwer, Md. Khalid; Gulati, Monica; Shen, Bairong; et al. (Frontiers in Cell and Developmental Biology, 2024)
Neuroblastoma (NB) is the most frequent solid tumor in pediatric cases, contributing to around 15% of childhood cancer-related deaths. The wide-ranging genetic, morphological, and clinical diversity within NB complicates the success of current treatment methods. Acquiring an in-depth understanding of genetic alterations implicated in the development of NB is essential for creating safer and more efficient therapies for this severe condition. Several molecular signatures are being studied as potential targets for developing new treatments for NB patients. In this article, we have examined the molecular factors and genetic irregularities, including those within insulin gene enhancer binding protein 1 (ISL1), dihydropyrimidinase-like 3 (DPYSL3), receptor tyrosine kinase-like orphan receptor 1 (ROR1) and murine double minute 2-tumor protein 53 (MDM2-P53) that play an essential role in the development of NB. A thorough summary of the molecular targeted treatments currently being studied in pre-clinical and clinical trials has been described. Recent studies of immunotherapeutic agents used in NB are also studied in this article. Moreover, we explore potential future directions to discover new targets and treatments to enhance existing therapies and ultimately improve treatment outcomes and survival rates for NB patients.